Accuracy of additive manufacturing in stomatology - Tang, Yao; Zhang, Yunfan; Meng, Zhaoqiang; Sun, Qiannan; Peng, Liying; Zhang, Lingyun; Lu, Wenhsuan; Liang, Wei; Chen, Gui; Wei, Yan (Frontiers in Bioengineering and Biotechnology, 2022)
With the rapid development of the three-dimensional (3D) printing technology in recent decades, precise and personalized manufacturing has been achieved gradually, bringing benefit to biomedical application, especially stomatology clinical practice. So far, 3D printing has been widely applied to prosthodontics, orthodontics, and maxillofacial surgery procedures, realizing accurate, efficient operation processes and promising treatment outcomes. Although the printing accuracy has improved, further exploration is still needed. Herein, we summarized the various additive manufacturing techniques and their applications in dentistry while highlighting the importance of accuracy (precision and trueness).